GE_GERICHTE P/6258/2024 vom 27. Juni 2024 - GE Cour de justice (2024)
ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;INFRACTIONS CONTRE L'HONNEUR;DROIT D'ÊTRE ENTENDU;DIFFAMATION | CP.173; CP.174; CPP.310; Cst.29.al2